Dynamics of the intensity of an affectively-hostile response in the structure of mental health disorders in blue-water sailors depending on the level of psychosocial stress they have experienced - Kosenko, Корнелія; Markova , Маріанна (Psychosomatic Medicine and General Practice, 2019)
The aim. The research aims to analyze the dynamics of the intensity of an affective-hostile response in the structure of mental health disorders in blue-water sailors, as a destructive response of the personality to overtime occupational stress factors, depending on the level of psychosocial stress (PS) they have experienced. The hypothesis. The hypothesis of the study was the statement about the connection between the level of PS and the severity of manifestations of aggression and hostility in this contingent. Contingent and research methods. In 2016-19 during the inter-cruise period, 300 blue-water sailors were surveyed, among whom were 200 representatives of the merchant marine fleet (110 members of the command and 90 sailors) and 100 employees of the Ukrainian sea passenger fleet (70 command and 30 privates). All examined were men, citizens of Ukraine. The study included the use of clinical-psychopathological and psychodiagnostic methods. Research results. It has been established that there is a close linear connection between the intensity of the aggressiveness phenomenon and the level of stress response inherent in the examined: an increase in the pathological stress load increases the severity of the manifestations of an aggressive response. The severity of the hostile response did not show any association with the level of PS experienced by the respondents. Besides, an incongruence was revealed between the average intensity indicators of aggressive and hostile tendencies for long-distance sailors: increased hostility against the background of a less pronounced general aggressiveness was characteristic of people with low and moderate levels of PS, created conditions that provoked an inability to constructively respond to existing destructive aggressive impulses (verbal and indirect aggression, resentment and suspicion), which contributed to its further pathological transformation with growing irritation and worsening of stress load and pathological response to it, and made it impossible to reverse the development of affective and behavioural manifestations of mental maladjustment, identified in most patients. Conclusion. The data obtained should be taken into account when developing specific measures of psychotherapy and psychoprophylaxis for this contingent, which is the prospect of this study.